GAS CHROMATOGRAPHY-MASS SPECTROMETRY/MASS SPECTROMETRY ANALYSIS OF TERMINALIA CATAPPA L. NUT AND ANTIMICROBIAL ASSAY - M, KRISHNAVENI; Kumari G, Krishna; M, Kalaivani; Banu C, Ragina (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The present study was carried out with the main objective of studying Terminalia catappa nut phyto-constituents through GC-MS/MS, as well as its antibacterial, antifungal activities. Methods: The T. catappa nut collected was shade dried and extracted with ethanol, the obtained ethanol extract was used for the whole study- GCMS/ MS, antimicrobial activity. Results: The results of GC-MS/MS showed 12 peaks. Among the 12 peaks obtained, the highest peak area percent of 48.58 for Propane, 1,1-diethoxyand 24.36% for t-Butyl hydrogen phthalate followed by 3-Isopropoxy-1,1,1,7,7,7-hexamethyl-3,5,5-tris (trimethylsiloxy) tetrasiloxane showing 12.80 as peak area percent and all the other compound was found to be moderate in peak area percent which was in the range of 3.52-1.10 except β-l- Arabinopyranoside methyl, and Cyclopropanecarboxylic acid, oct-3-en-2-yl ester as its peak area percent was very low showing 0.08 and 0.13. The antibacterial activity was good with Escherichia coli when compared to Staphylococcus aureus likewise, the antifungal activity was good with Candida albicans on comparison with Aspergillus niger. Conclusion: The naturally occurring non –nutrient plant chemicals called as phytochemicals especially phenolics – a natural antioxidant contained in T. catappa nut would have contributed for its antibacterial, antifungal properties by interfering with the phospholipid bilayer of the cell membrane and destroying the enzymes required for cellular processes ensuring its therapeutic potential. The variation in therapeutic potential depends on the nutrient content of the soil and other climatic conditions. This confirms the need, validity for phytochemical characterization via analytical methods. Keywords: Antimicrobial, Analytical, Gas chromatography-mass spectrometry/MS, Terminalia sp.